The use of indocyanine green to detect sentinel nodes in breast cancer: A prospective study. Issue 1 (January 2015) - Samorani, D.; Fogacci, T.; Panzini, I.; Frisoni, G.; Accardi, F.G.; Ricci, M.; Fabbri, E.; Nicoletti, S.; Flenghi, L.; Tamburini, E.; Tassinari, D.; Gianni, L.
Abstract Background Although Indocyanine green (ICG) is used to find sentinel nodes (SN) in patients with breast cancer (BC), its role in clinical practice is still debated, and needs a definitive validation to be included in the standard approach to finding sentinel nodes in breast cancer. Materials and methods To validate the ICG methods of detecting the SN in BC we have recently concluded a prospective validation trial. Patients with clinically node-negative, invasive early BC scheduled for breast surgery and SN biopsy were included in the trial. All the patients underwent SN detection using both the standard-of-care procedure using radioisotope technetium (99mTc) and the ICG, using the Photodynamic Eye camera. A comparison of the detection rate and the diagnostic accuracy of the two methods was performed to detect the equivalency of the two approaches. Results At the end of the enrolment, 301 patients were considered eligible and included in the trial, and 589 nodes were removed. Five hundred and eighty-three nodes (99%) were identified with ICG (median 2 nodes per patient) and 452 (76.7%) were identified with 99mTc (median 2 nodes per patient). A concordance index of 98.75% (CI, 95% = 97.1%–99.5%) was detected. The dosage given ranged from 0.3 to 1.4 ml. ICG was used in all patients eligible for SN biopsy without any significant acute side effects. Conclusions The index of concordance between 99mTc and ICG seems to be extremely high, suggesting that ICG could be validated as an alternative method to 99mTc in the detection of SN in BC.